Comparison of titanium elastic nailing and spica casting outcomes in preschool children following femoral diaphyseal fractures - Muahmmad Ikram; Sajid Ejaz Rao; Nadia Gul; Sadia Ijaz; Munawer Latif Memon; Sohail Muzammil (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Pediatric femoral diaphyseal fractures are common fractures in preschool children. The titanium elastic nailing technique is becoming prevalent in developed and developing countries. To compare the frequency of efficacy, safety and mean surgical fixation outcomes among patients who underwent titanium elastic nailing versus spica casting in diaphyseal femur fracturesMETHODOLOGY: A prospective study was conducted at department of orthopedics, Pakistan Ordinance Factory (POF) hospital. The study duration was 2 years (March 2018-March 2020). A sample size of 42 children was calculated using WHO calculator. Children selection was made on the basis of non-probability (consecutive) sampling. Group TEN underwent titanium elastic nailing, while group SPICA underwent hip spica casting. Patients were followed for six months. We used SPSS version 24 for the analysis of data. Fisher exacts and independent T-test were applied for measuring associations and comparisons of two groups. P-value ≤0.05 was considered significant.RESULTS: Total of 42 patients were included in the study. The mean age of patients was 3.4 years±1.4SD. The TEN group showed satisfactory results in malalignment (p=0.000) and complications (p=0.000). SPICA group showed significantly high assisted weight bearing duration (p=0.000), full weight bearing duration (p=0.000), greater operative time (p=0.000), lower range of motion (p=0.000) and less patient satisfaction (p=0.000) as compared to TEN group.CONCLUSION: Titanium elastic nailing is safe, effective, and allows faster recovery in pediatric patients with diaphyseal femoral fractures. We recommend titanium elastic nailing as a valid treatment option for femur fractures in preschool children.